Steel slag-slag-based cementitious material based on early hydration degree regulation and pre-hydration-carbon dioxide mineralization combined curing, preparation method and application thereof
Patent Information
- Application Number
- CN202611376051.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]针对上述现有技术存在的不足,本发明的目的在于提供基于早期水化程度调控的预水化—二氧化碳矿化复合养护钢渣—矿渣基胶凝材料及其制备方法和应用,以解决现有多源固废胶凝材料中钢渣早期活性不足、单纯水化强度发展慢、过早或过晚矿化影响结构形成、以及二氧化碳矿化介入时机缺乏可操作判据的问题
[0023]与现有技术相比,本发明的有益效果至少包括如下几个方面:
Smart Images

Figure CN123003201A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of solid waste resource utilization, carbon dioxide mineralization curing, and low-carbon cementitious material preparation technology, specifically to a pre-hydration-carbon dioxide mineralization composite curing steel slag-blast furnace slag-based cementitious material based on early hydration degree control, its preparation method, and its application. The material uses steel slag, blast furnace slag, alkali slag, and carbide slag as main raw materials, and the timing of carbon dioxide mineralization intervention is determined by the early hydration degree. Background Technology
[0002] Steel slag, blast furnace slag, alkali slag, and calcium carbide slag are all bulk industrial solid wastes generated by the iron and steel, building materials, and chemical industries. Steel slag contains components such as C2S, C3S, free calcium oxide, calcium hydroxide, RO phase, and iron phase, and has certain hydratable activity and can be used as a source of calcium carbide. Blast furnace slag is mainly composed of amorphous aluminosilicate glass phase and has high potential hydraulic properties. Alkali slag and calcium carbide slag contain a large amount of CaO, Ca(OH)2, salts, and alkaline components, which can provide an alkaline environment and calcium source for the blast furnace slag-steel slag system. Utilizing the above solid wastes to construct low-carbon cementitious materials is beneficial for reducing cement clinker usage and improving the resource utilization level of solid waste.
[0003] However, steel slag contains some silicate minerals with slow hydration kinetics and a high amount of low-activity components such as RO phase. When the steel slag content increases, the system is prone to problems such as slow early structure formation, insufficient pore connectivity, and limited mechanical property development. Traditional solutions often use NaOH, water glass, or cement clinker as activating components, but these solutions have problems such as high cost, strong corrosiveness, high carbon emissions, or being unfavorable for the complete solid waste treatment.
[0004] Carbon dioxide mineralization curing can convert calcium-containing components in steel slag and carbide slag into stable carbonates such as CaCO3, thereby filling pores and improving early strength. However, if mineralization is carried out immediately after mixing, the initial hydration framework has not yet formed inside the billet, and the carbonate deposits are unlikely to form a continuous load-bearing structure with the hydration products. If the hydration time is too long, a large amount of hydration products after the main hydration peak will reduce the carbon dioxide diffusion channels, causing uneven carbonation or hindering subsequent hydration. Therefore, carbon dioxide mineralization curing cannot achieve the best results simply by extending the time or increasing the concentration; the key is to rationally determine the timing of mineralization intervention.
[0005] A search revealed that among existing publicly available technologies, CN104478256A / B discloses a technical solution for preparing magnesium-calcium carbonate cementitious materials by CO2 carbonation of industrial alkaline waste residue, active magnesium oxide, and cement. Its focus is on the MgO / cement-type carbonate cementitious system, rather than the early hydration degree control of the steel slag-mineral slag-alkali slag-carbide slag system. CN114538806A discloses a hydration-carbonation composite hardening cementitious material based on steel slag, whose raw materials include cement clinker, pretreated carbide slag, bentonite, and an accelerator. This technical route relies on clinker and accelerators and does not determine the timing of CO2 mineralization intervention based on the exothermic characteristics of hydration. CN112266264B discloses aerated concrete based on the synergistic effect of alkali activation and accelerated carbonation, which includes a foaming agent and a foam stabilizer. Its application is in lightweight aerated concrete, which differs from the high-density cementitious material of this invention. CN112429982B discloses a cementitious material based on wet-based alkaline slag-wet-based calcium carbide slag-activated slag. It mainly utilizes alkaline slag and calcium carbide slag to activate the slag and form its strength, but does not address the carburizable calcium source from steel slag, the timing of carbon dioxide mineralization intervention, or the synergistic control of subsequent standard curing. CN111875332A discloses a method for preparing carbonized bricks using wet-milled calcium carbide slag. Its carbonization target is mainly calcium carbide slag slurry, which is used for brick making. However, it does not solve the matching problem between early hydration and CO2 mineralization in the quaternary solid waste system of steel slag-slag-alkaline slag-calcium carbide slag.
[0006] In summary, although existing technologies involve steel slag carbonization, alkali slag / carbide slag activated slag, carbonized bricks or hydration carbonization composite hardening materials, they generally lack technical solutions that couple the “composite solid waste activation system, early hydration degree determination, CO2 mineralization curing and subsequent standard curing” as a whole process. Summary of the Invention
[0007] To address the shortcomings of the existing technologies, the present invention aims to provide a pre-hydration-carbon dioxide mineralization composite curing steel slag-slag-based cementitious material based on early hydration degree regulation, its preparation method, and its application. This addresses the problems of insufficient early activity of steel slag, slow development of simple hydration intensity, impact of premature or late mineralization on structure formation, and lack of operable criteria for determining the timing of carbon dioxide mineralization intervention in existing multi-source solid waste cementitious materials.
[0008] To achieve the above technical objectives, the present invention adopts the following technical solution: This invention provides a method for preparing a pre-hydrated-carbon dioxide mineralization composite curing steel slag-slag-based cementitious material based on early hydration degree control. The preparation method of this invention does not involve the addition of cement clinker, sodium hydroxide, water glass, foaming agent, or foam stabilizer, and includes the following steps:
[0009] Step 1, Raw Material Pretreatment: Steel slag, blast furnace slag, alkali slag, and calcium carbide slag are dried, ground, and screened respectively to obtain steel slag powder, blast furnace slag powder, alkali slag powder, and calcium carbide slag powder. The steel slag is selected from one or more of converter steel slag, electric furnace steel slag, and steel slag tailings after magnetic separation, preferably converter steel slag after crushing, magnetic separation, and aging. The blast furnace slag is granulated blast furnace slag powder, the alkali slag is a by-product of the ammonia-soda process for alkali production, and the calcium carbide slag is produced during the hydrolysis of calcium carbide to produce acetylene.
[0010] Step 2, compound solid waste batching: Weigh each raw material according to the total mass of the cementitious components, weigh 35%~65% of steel slag powder, 20%~55% of slag powder, 5%~15% of alkali slag powder and 2%~10% of calcium carbide slag powder, and the sum of the mass percentages of each raw material is 100%.
[0011] Step 3, Low Water-to-Binder Ratio Slurry Preparation and Molding: After premixing the above powder raw materials evenly, add mixing water and polycarboxylate-based water-reducing agent and stir. The water-to-binder ratio is 0.12~0.20, that is, the mass ratio of mixing water to gelling components is 0.12~0.20:1, and the water-reducing agent dosage is 0.5%~1.5% of the total mass of gelling components. The resulting gel mixture is poured, vibrated, or pressed into shape and retained in the mold for pre-hydration, allowing the green body to form an initial hydration skeleton. The timing for carbon dioxide mineralization intervention is reached. c Demolding afterward; when the blank is at t c If all demolding conditions are already met, demolding can be done ahead of schedule, and pre-hydration can continue until the desired temperature is reached. c .
[0012] Step 4, Early Hydration Degree Determination: Isothermal calorimetry tests are performed on gelled mixtures made from the same formula and batch of raw materials. The test temperature is the same as the pre-hydration curing temperature, the test time is no less than 72 hours, and the main accelerating hydration peak is covered. The cumulative heat release curve and heat release rate curve are obtained, and an isothermal calorimetry baseline curve is established. Timing of Carbon Dioxide Mineralization Intervention (t) c Simultaneously satisfying: 0.30≤Q(t) c ) / Q 72 ≤0.55, t p -t c ≥8 h and q(t c )≤0.60q p The above criteria are used to identify the intervention stage where an initial hydration framework has been formed but has not yet entered the main accelerated hydration peak, and do not use a fixed 24-hour period as the only time point under all raw material sources and ratios.
[0013] Step 5, Carbon dioxide mineralization curing: to reach t cThe billets are then demolded and immediately placed in a closed-loop carbon dioxide mineralization device under atmospheric pressure. Spacing is maintained between the billets, and all surfaces are exposed to the atmosphere. First, carbon dioxide is introduced to replace the air in the device, then carbon dioxide is continuously replenished to maintain a set volume fraction. The carbon dioxide volume fraction is 20%–100%, the temperature is 40°C–70°C, the relative humidity is 50%–90%, and the mineralization time is 2–12 hours; preferably, the carbon dioxide volume fraction is 100%, the temperature is 60°C, and the mineralization time is 8 hours.
[0014] Step Six, Subsequent Standard Curing: After carbon dioxide mineralization, the mineralized green body is transferred to a standard curing environment with a temperature of 20±2 ℃ and a relative humidity of not less than 95% for continued curing. Unreacted steel slag and ore hydrate further, forming C-(A)-SH gel, AFt, and other aluminum-containing hydration products. When chlorine-containing components participate in the reaction, AFm-type chlorine-containing bound phases can be formed, which, together with the carbonates formed in the previous mineralization, promote structural densification.
[0015] Preferably, the specific surface area of the steel slag powder is 350 m². 2 / kg~550 m 2 / kg, the specific surface area of slag powder is 350 m² 2 / kg~550 m 2 / kg, D of alkaline slag powder and calcium carbide slag powder 50 All are no larger than 30 μm.
[0016] Preferably, the steel slag powder is weighed at 40%~60%, the slag powder at 25%~45%, the alkali slag powder at 8%~12%, and the calcium carbide slag powder at 4%~8%, and the sum of the mass percentages of each raw material is 100%.
[0017] Preferably, the gelled mixture is formed by casting, vibration compaction, or pressing; after molding, it is left to stand in the mold and placed in an environment with a relative humidity of not less than 90% for pre-hydration curing until it reaches t c After demolding, carbon dioxide mineralization was immediately carried out.
[0018] Preferably, the pre-hydration curing conditions are 20±2 ℃ and relative humidity not less than 90%; under these conditions, the timing of carbon dioxide mineralization intervention to meet the three isothermal calorimetric criteria is usually 18 h to 30 h after molding.
[0019] Preferably, carbon dioxide mineralization curing employs either carbon dioxide concentration maintenance-type mineralization curing or alternating ventilation-humidification mineralization curing. Carbon dioxide concentration maintenance-type mineralization curing involves continuously supplementing carbon dioxide during mineralization to maintain a set concentration, while alternating ventilation-humidification mineralization curing alternates between carbon dioxide ventilation and humidification balancing phases. The temperature (t) is determined using a pre-established isothermal calorimetric reference curve based on the same formulation and batch of raw materials. c There is no need to perform online calorimetry testing on each batch of molded blanks.
[0020] This invention also protects the pre-hydration-carbon dioxide mineralization composite curing steel slag-slag-based cementitious material prepared by the above method based on early hydration degree control.
[0021] Preferably, taking the time of water addition and mixing as the starting point of the curing period, the compressive strength of the material at 32 h is not less than 29 MPa and the compressive strength at 56 d is not less than 50 MPa; compared with the control material with the same formula, temperature and humidity and without carbon dioxide mineralization, the net increase of CaCO3 calculated according to the mass loss at 500 ℃~900 ℃ in the TG-DTG test is 2.0%~4.6%.
[0022] This invention also protects the application of the pre-hydration-carbon dioxide mineralization composite curing steel slag-slag-based cementitious material based on early hydration degree regulation as a cementing component in the preparation of precast components, blocks or panels.
[0023] Compared with the prior art, the beneficial effects of the present invention include at least the following aspects: 1. This invention uses steel slag and blast furnace slag as the main raw materials, and alkali slag and carbide slag as composite activating components. The timing of carbon dioxide mineralization intervention is determined based on the isothermal calorimetric reference curve of the mixture with the same formula. This allows the green body to be demolded and subjected to short-term mineralization curing at a stage where the initial hydration framework has been formed but the main accelerated hydration peak has not yet appeared, followed by standard curing. This "pre-hydration-mineralization-subsequent hydration" composite curing process significantly improves the early compressive strength of the material and maintains continuous development of later-stage strength without relying on cement clinker, sodium hydroxide, or water glass.
[0024] 2. This invention constructs a quaternary solid waste cementing system from steel slag, blast furnace slag, alkaline slag, and carbide slag. Alkaline slag and carbide slag provide an alkaline environment, calcium source, and sulfate / chloride regulation. Steel slag provides a carbonizable calcium source and potential hydration components. Blast furnace slag provides a continuously reacting silicon and aluminum source. This system does not rely on cement clinker, NaOH, or water glass.
[0025] 3. This invention does not simply specify a fixed pre-hydration time, but uses three dimensionless or relative criteria—cumulative heat release ratio, time interval from the main accelerated hydration peak, and heat release rate at the intervention time—to jointly determine the timing of carbon dioxide mineralization intervention, thereby adapting to the differences in reaction rates caused by different steel slag activities, slag ratios, and solid waste sources.
[0026] 4. The present invention performs carbon dioxide mineralization before the main accelerated hydration peak appears, so that the unreacted active calcium phase and carbon dioxide transport channels are still retained inside the green body, and the initial hydration framework has been formed, which is conducive to the continuous deposition of carbonate and the growth of subsequent hydration products.
[0027] 5. This invention fills the pores and provides nucleation sites by forming carbonates such as CaCO3 through carbon dioxide mineralization. Subsequent standard curing promotes the continued generation of C-(A)-SH gel, AFt and other aluminum-containing hydration products, thereby improving the insufficient early performance under simple carbonization or simple hydration conditions.
[0028] 6. The present invention can significantly improve early compressive strength because: the initial skeleton formed by prehydration provides an early load-bearing foundation; stable carbonates such as CaCO3 generated by carbon dioxide mineralization play a role in filling, cementing and nucleating at pores and particle interfaces; and subsequent hydration further promotes structural densification; at the same time, by generating stable carbonates to fix carbon dioxide and realize the synergistic disposal of multi-source solid waste, it is suitable for precast components, blocks and panels. Attached Figure Description
[0029] Figure 1 These are schematic diagrams illustrating the determination of the timing of carbon dioxide mineralization intervention based on the early degree of hydration in Examples 1 to 3 of the present invention. Detailed Implementation
[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] In this invention, Q(t) c (Pre-hydration to t) c The cumulative heat released at time Q 72 The cumulative heat release of the same formula mixture over 72 hours is t p To exclude the appearance time of the main accelerated hydration peak after the initial wetting and dissolution peak, q(t) c ) for t c The rate of heat release during hydration, q pThe peak heat release rate of the hydration peak is accelerated. The isothermal calorimetry test temperature is the same as the pre-hydration curing temperature, and the cumulative heat release and heat release rate are normalized according to the mass of the cementitious components. The condition 0.30 ≤ Q(t) is satisfied. c ) / Q 72 ≤0.55, t p -t c ≥8 h and q(t c )≤0.60q p The time period can be considered as the mineralization intervention stage; the 24 hours in the example is only the engineering implementation time point when the three formulations jointly meet the criteria, and is not the fixed optimal time for all raw material batches.
[0032] To further illustrate the differences between this invention and related published patents, the following examples are provided: Table 1. Differences between this invention and related prior art patents The present invention will be further described below with reference to the embodiments.
[0033] Example 1 The preparation method of pre-hydrated-carbon dioxide mineralization composite curing steel slag-slag based cementitious material (40% steel slag admixture system) based on early hydration degree regulation includes the following steps: This embodiment uses slag, steel slag, alkali slag and calcium carbide slag as raw materials. The slag is granulated blast furnace slag powder, the steel slag is converter steel slag powder, the alkali slag is the by-product of the ammonia-soda process for alkali production, and the calcium carbide slag is the by-product of the calcium carbide hydrolysis process for acetylene production. All raw materials are dried and ground before use.
[0034] S1. Weigh the raw materials according to the total mass of the cementitious components, weigh 40% steel slag powder, 45% blast furnace slag powder, 10% alkali slag powder and 5% calcium carbide slag powder, premix the powder raw materials, add mixing water and water-reducing agent, and stir to obtain cementitious slurry; wherein, the water-cement ratio is 0.15, and the dosage of polycarboxylate water-reducing agent is 1.0%.
[0035] S2. Pour the gel mixture into a 20 mm × 20 mm × 20 mm mold and vibrate to form it. Perform pre-hydration curing in the mold to obtain the green body.
[0036] S3. The green body is pre-hydrated at 20±2 ℃ and relative humidity not less than 90%. Based on the 72 h isothermal calorimetry results of the same formula gelling paste, the 24 h (t) c The cumulative heat release Q (24 h) is 83 J·g. −1 The cumulative heat release Q over 72 hours 72 220 J·g −1 Q(24 h) / Q 72The value is 0.377; the peak value of the main exothermic peak (q) p The value was 4.52 mW·g −1 Peak time (t) p The duration is 43.5 h, t p -t c =19.5 h; the heat release rate q(24 h) at 24 h is approximately 0.89 mW·g, as read from the heat release rate curve. −1 ,q(24 h) / q p It is approximately 0.20, lower than 0.60, and t c The main peak has not yet appeared. The above results simultaneously satisfy the three criteria of cumulative heat release ratio, time from the main peak, and heat release rate, that is, the actual determined t c When 0.30≤Q(t) is satisfied c ) / Q 72 ≤0.55, t p -t c ≥8h and q(t c )≤0.60q p All time periods fall within the intervention window.
[0037] After pre-hydration for 24 hours, the green body was demolded and immediately placed in a closed-loop carbon dioxide mineralization curing device under normal pressure. All surfaces of the green body were exposed to the atmosphere. Carbon dioxide was first introduced to replace the air in the device, and then continuously replenished to maintain a 100% volume fraction. The mineralization temperature was 60℃, the relative humidity was controlled at 50%–90%, and the mineralization time was 8 hours. After mineralization, the samples were transferred to a standard curing environment with a temperature of 20±2℃ and a relative humidity not lower than 95%. The compressive strength age was calculated from the time of water addition and tested at 32 hours, 7 days, 28 days, and 56 days.
[0038] Example 2 The preparation method of pre-hydrated-carbon dioxide mineralization composite curing steel slag-slag based cementitious material (50% steel slag admixture system) based on early hydration degree regulation includes the following steps: This embodiment is the same as Embodiment 1 in terms of raw material source, pretreatment method, molding method, demolding time, carbon dioxide mineralization conditions and subsequent standard curing conditions. The difference is that the mass ratio of the cementitious components is 50% steel slag powder, 35% slag powder, 10% alkali slag powder and 5% calcium carbide slag powder.
[0039] Based on the 72-hour isothermal calorimetric results of the same formula gelatinous paste, 24 h (t) c The cumulative heat release Q (24 h) is 96 J·g. −1 The cumulative heat release Q over 72 hours 72 225 J·g −1Q(24 h) / Q 72 It is 0.427; the peak value of the main exothermic peak (q) p The value was 4.18 mW·g −1 Peak time (t) p The duration is 44.5 h, t p -t c =20.5 h; the heat release rate q(24h) was approximately 0.82 mW·g at 24h, as read from the heat release rate curve. −1 ,q(24 h) / q p It is approximately 0.20, lower than 0.60, and t c The main peak has not yet appeared. The above results simultaneously satisfy the three criteria of cumulative heat release ratio, time from the main peak, and heat release rate, that is, the actual determined t c When 0.30≤Q(t) is satisfied c ) / Q 72 ≤0.55, t p -t c ≥8h and q(t c )≤0.60q p The time periods all fall within the intervention window. 24 hours is also within this window. Figure 1 The middle of the intervention window shown has already formed the initial hydration framework but has not yet entered the main accelerated hydration peak. Therefore, 24 hours after formation is also selected as the timing for CO2 mineralization intervention.
[0040] Example 3 The preparation method of pre-hydrated-carbon dioxide mineralization composite curing steel slag-slag based cementitious material (60% steel slag admixture system) based on early hydration degree regulation includes the following steps: This embodiment is the same as Embodiment 1 in terms of raw material source, pretreatment method, molding method, demolding time, carbon dioxide mineralization conditions and subsequent standard curing conditions. The difference is that the mass ratio of the cementitious components is 60% steel slag powder, 25% slag powder, 10% alkali slag powder and 5% calcium carbide slag powder.
[0041] Based on the 72-hour isothermal calorimetric results of the same formula gelatinous paste, 24 h (t) c The cumulative heat release Q (24 h) is 98 J·g. −1 The cumulative heat release Q over 72 hours 72 200 J·g −1 Q(24 h) / Q 72 The value is 0.490; the peak value of the main exothermic peak (q) p The value is 3.30 mW·g −1 Peak time (t) p The duration was 47.0 h, t p -t c=23.0 h; the heat release rate q(24h) was approximately 0.70 mW·g at 24h, as read from the heat release rate curve. −1 ,q(24 h) / q p It is approximately 0.21, lower than 0.60, and t c The main peak has not yet appeared. The above results simultaneously satisfy the three criteria of cumulative heat release ratio, time from the main peak, and heat release rate, that is, the actual determined t c When 0.30≤Q(t) is satisfied c ) / Q 72 ≤0.55, t p -t c ≥8h and q(t c )≤0.60q p All time periods fall within the intervention window.
[0042] Compared with Examples 1 and 2, the main peak value of Example 3 was 4.52 mW·g −1 and 4.18 mW·g −1 Reduced to 3.30 mW·g −1 The main peak time was delayed from 43.5 h and 44.5 h to 47.0 h, indicating that the higher steel slag content reduced and delayed the subsequent accelerated hydration peak; however, its Q(24 h) / Q 72 It remains within the range of 0.30 to 0.55, and t p -t c and q(24 h) / q p All criteria were met, therefore 24 hours is still considered a suitable stage for carbon dioxide mineralization intervention.
[0043] Figure 1 The gray area represents the common intervention stage where all three criteria are met in Examples 1-3. 24 hours falls within this stage and facilitates the unified implementation of the three formulations; therefore, Examples 1-3 all opted for demolding and carbon dioxide mineralization 24 hours after molding. The q(24 h) values for Examples 1-3 at 24 h are approximately 0.89 mW·g. −1 0.82 mW·g −1 and 0.70 mW·g −1 ,q(24 h) / q p They are approximately 0.20, 0.20 and 0.21 respectively, all lower than 0.60.
[0044] The data for the early hydration degree criteria of Examples 1 to 3 are shown in Table 2.
[0045] Table 2. Criteria for Early Hydration Degree and Timing of CO2 Mineralization Intervention To verify the reinforcing effect of carbon dioxide mineralization on prehydrated materials, a comparative example without carbon dioxide mineralization was set up. The mass ratio of the cementitious components in Comparative Example 1 was the same as in Example 1; Comparative Examples 2 and 3 were the same as in Examples 2 and 3, respectively. Each comparative example was demolded 24 h after molding and simultaneously cured for 8 h in the same curing device using air instead of carbon dioxide, under the same temperature, relative humidity, and time conditions as the corresponding examples, and then transferred to standard curing.
[0046] The compressive strength of the examples and comparative examples is shown in Table 3. The compressive strength age was calculated from the time of water addition and mixing, with the 32-hour age consisting of 24-hour pre-hydration and 8-hour mineralization or control curing. A universal testing machine was used, with continuous loading at a displacement rate of 0.5 mm / min until failure; each test group had at least three parallel specimens, and the arithmetic mean was taken. As shown in Table 3, carbon dioxide mineralization had the most significant effect on the 32-hour strength improvement, with Examples 1, 2, and 3 showing increases of 84.8%, 85.1%, and 94.7% compared to the comparative examples, respectively; the examples continued to develop strength at 56 days. The existing data are used to demonstrate the enhancing effect of mineralization after 24-hour pre-hydration, and are not used to claim that 24 hours is the only optimal intervention time under all raw material and proportion conditions.
[0047] Table 3 Compressive strength results of the examples and comparative examples To eliminate the influence of carbonates inherent in the raw materials and natural carbonization, the CO2 solids content in this example was calculated by the net CaCO3 increment of the carbonized group relative to the corresponding uncarbonized control group. The net CaCO3 increment was obtained by converting the mass loss in the 500 ℃~900 ℃ range during TG-DTG testing.
[0048] As shown in Table 4, the net CaCO3 increments at the mineralization completion age for Examples 1, 2, and 3 were 2.08%, 4.53%, and 3.84%, respectively, corresponding to net CO2 sequestration of 9.2 kg CO2·t. −1 binder, 19.9 kg CO2·t −1 binder and 16.9 kg CO2·t −1 binder; Further conversion yields a unit carbon sequestration rate of 22.9 kg CO2·t. − 1 steel slag, 39.9 kg CO2·t −1 steel slag and 28.2 kg CO2·t −1 The results indicate that a moderate steel slag content is more conducive to achieving a balance between the supply of carbideable calcium source and CO2 transport.
[0049] Table 4. CO2 Sedimentation and Carbon Sedimentation per Unit of Steel Slag in Examples In actual engineering production, the f-CaO, C2S / C3S content, RO phase content, and grinding fineness of steel slag from different sources vary, leading to differences in the early hydration exothermic curves. This invention does not limit the timing of CO2 mineralization intervention to a fixed 24 hours, but rather uses Q(t) to... c ) / Q 72 t p -t c and q(t c ) / q p Criteria determine the appropriate intervention stage. When the raw material has high activity, t c The reaction time can be advanced to 18-22 hours; when the steel slag content is high or the slag reaction is slow, the reaction time can be advanced to 18-22 hours. c The timeframe can be extended to 24-30 hours. This method of limiting CO2 intervention by a hydration degree window rather than a single time point improves the repeatability under different raw material batches and different steel slag admixture conditions, and further highlights the inventiveness and implementation stability of this invention compared to a fixed carbonation time process.
[0050] The carbon dioxide mineralization conditions can be adjusted according to the product size and target strength. When the product size is small or the pore connectivity is good, mineralization conditions of 20%~60% CO2, 40℃~60℃, and 4h~8h can be used. When it is necessary to improve the early demolding strength or carbon fixation, mineralization conditions of 80%~100% CO2, 50℃~70℃, and 6h~12h can be used. After mineralization, standard curing or moisturizing curing should be carried out to avoid excessive carbonization and insufficient subsequent hydration.
[0051] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A method for preparing a pre-hydration-carbon dioxide mineralization composite curing steel slag-slag-based cementitious material based on early hydration degree regulation, characterized in that, Includes the following steps: Weigh the raw materials according to the following mass percentages: 35%~65% steel slag powder, 20%~55% blast furnace slag powder, 5%~15% alkaline slag powder, and 2%~10% calcium carbide slag powder, with the sum of the mass percentages of each raw material being 100%. Premix the powder raw materials to obtain the gelling component, add mixing water and water-reducing agent, stir to obtain a low water-to-binder ratio gelling mixture, shape the gelling mixture and pre-hydrate and cure it in the mold to obtain the green body; The timing of carbon dioxide mineralization intervention (t) was determined based on the isothermal calorimetric reference curve of the gelled mixture with the same formulation. c The t c Simultaneously satisfying: 0.30≤Q(t) c ) / Q 72 ≤0.55, t p -t c ≥8 h and q(t c )≤0.60q p ; where Q(t) c (Pre-hydration to t) c The cumulative heat released at time Q 72 The cumulative heat release over 72 hours, t p To accelerate the appearance time of the hydration peak, q(t) c ) for t c The rate of heat release during hydration, q p To accelerate the peak heat release rate of the hydration peak; The timing for carbon dioxide mineralization intervention t c Then, the billet is demolded to expose all surfaces, and immediately placed in a carbon dioxide atmosphere for mineralization curing to obtain a mineralized billet. The mineralized billet is subjected to standard curing or moisturizing curing to obtain the pre-hydration-carbon dioxide mineralization composite curing steel slag-slag-based cementitious material based on early hydration degree control.
2. The preparation method according to claim 1, characterized in that, Steel slag is one or more of converter steel slag, electric furnace steel slag, and steel slag tailings after magnetic separation; blast furnace slag is granulated blast furnace slag powder; alkali slag is the by-product of ammonia-soda process for alkali production; and calcium carbide slag is the calcium carbide slag produced during the hydrolysis of calcium carbide to produce acetylene.
3. The preparation method according to claim 1, characterized in that, The specific surface area of steel slag powder is 350 m². 2 / kg~550m 2 / kg, the specific surface area of slag powder is 350 m² 2 / kg~550 m 2 / kg, D of alkaline slag powder and calcium carbide slag powder 50 All are no larger than 30 μm.
4. The preparation method according to claim 1, characterized in that, Weigh the raw materials according to the following mass percentages: 40%~60% steel slag powder, 25%~45% blast furnace slag powder, 8%~12% alkali slag powder, and 4%~8% calcium carbide slag powder. The sum of the mass percentages of each raw material is 100%.
5. The preparation method according to claim 1, characterized in that, The mass ratio of mixing water to cementitious components is 0.12~0.20:
1. The water-reducing agent is a polycarboxylate-based water-reducing agent, and the dosage of the water-reducing agent is 0.5%~1.5% of the total mass of the cementitious components.
6. The preparation method according to claim 1, characterized in that, The isothermal calorimetry test temperature is the same as the pre-hydration curing temperature, and the isothermal calorimetry test time is not less than 72 h and covers the main accelerated hydration peak; the cumulative heat release and heat release rate are normalized according to the mass of the gelling components; the main accelerated hydration peak is the local peak with the largest peak heat release rate during the test period after excluding the initial wetting and dissolution peak of mixing.
7. The preparation method according to claim 1, characterized in that, The pre-hydration curing conditions are 20±2 ℃ and relative humidity not less than 90%. Under these conditions, 0.30≤Q(t) is satisfied. c ) / Q 72 ≤0.55, t p -t c ≥8 h and q(t c )≤0.60q p The timing for carbon dioxide mineralization intervention is 18 h to 30 h after formation.
8. The preparation method according to claim 1, characterized in that, Carbon dioxide mineralization curing is carried out in an atmospheric pressure closed mineralization device. First, carbon dioxide is introduced to replace the air in the device, and then carbon dioxide is continuously replenished to maintain the set volume fraction. Spacing is left between the billets and all surfaces are exposed to the atmosphere. The carbon dioxide volume fraction is 20%~100%, the temperature is 40℃~70℃, the relative humidity is 50%~90%, and the mineralization curing time is 2 h~12 h.
9. A pre-hydration-carbon dioxide mineralization composite curing steel slag-slag-based cementitious material based on early hydration degree control, characterized in that, The steel slag-slag-based cementitious material prepared by the preparation method according to any one of claims 1 to 8 is obtained; taking the time of water addition and mixing as the starting point of the curing period, the 32-h compressive strength of the pre-hydration-carbon dioxide mineralization composite curing material based on early hydration degree control is not less than 29 MPa, and the 56-day compressive strength is not less than 50 MPa.
10. The application of the pre-hydration-carbon dioxide mineralization composite curing steel slag-slag-based cementitious material based on early hydration degree regulation as described in claim 9 as a cementing component in the preparation of precast components, blocks or panels.
Citation Information
Patent Citations
Calcium-magnesium carbonate gel material and preparation method thereof
CN104478256A
Method for preparing carbonized brick from wet-milling carbide slag
CN111875332A
Autoclaved aerated concrete based on the synergistic effect of alkali activation and accelerated carbonation and its preparation method
CN112266264B
Cementitious materials, mortar materials and their preparation methods based on wet-based alkaline slag and wet-based carbide slag
CN112429982B
Hydrated and carbonized composite hardened cementing material based on steel slag and preparation method of hydrated and carbonized composite hardened cementing material
CN114538806A